2007
DOI: 10.1002/hipo.20267
|View full text |Cite
|
Sign up to set email alerts
|

GABAB receptor blockade enhances theta and gamma rhythms in the hippocampus of behaving rats

Abstract: The participation of GABA(B) receptors in hippocampal EEG generation was studied by intracerebroventricular (icv) and intracerebral infusions of GABA(B) receptor antagonist p-(3-aminopropyl)-p-diethoxymethyl-phosphinic acid (CGP35348) in freely behaving rats. During awake-immobility, icv CGP35348 induced a theta rhythm and increased gamma waves (30-100 Hz) in the hippocampus. The immobility theta peaked at 6-7 Hz and had a theta phase in CA1 stratum radiatum of approximately 160 degrees with reference to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 65 publications
5
23
0
1
Order By: Relevance
“…For example, animal studies have shown that administration of GABA B receptor agonists such as baclofen eliminates g-oscillations in rat hippocampal slices , whereas the blockade of GABA B receptors has been shown to enhance the g-oscillations in the hippocampus of behaving rats (Leung and Shen, 2007). Consistent with these studies, the stimulus-induced attenuation of g-oscillations was enhanced following the injection of tiagabine .…”
Section: Introductionmentioning
confidence: 73%
“…For example, animal studies have shown that administration of GABA B receptor agonists such as baclofen eliminates g-oscillations in rat hippocampal slices , whereas the blockade of GABA B receptors has been shown to enhance the g-oscillations in the hippocampus of behaving rats (Leung and Shen, 2007). Consistent with these studies, the stimulus-induced attenuation of g-oscillations was enhanced following the injection of tiagabine .…”
Section: Introductionmentioning
confidence: 73%
“…CGP concentrations of 0.1 to 1 mM used in this study were based on previous reports that (a) intrahippocampal infusion of 20 - 30 μM CGP permitted study of the effect of GABA B R blockade on theta and gamma rhythms in freely behaving rats (Leung and Shen, 2007), and (b) perfusion of 0.3 - 1 mM CGP in Mg 2+ -free medium evoked increases of extracellular guanosine 3′,5′-cyclic monophosphate (cGMP) without causing behavioral seizures (Fedele et al, 1997). The present study is the first in vivo demonstration that perfusion of 0.1 mM CGP in the hippocampal CA3/CA1 region is sufficient to block the presynaptic GABA B(1a,2) heteroreceptor resulting in GLU ECF elevation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Future experiments may test the causal role of OFC theta oscillatory activity in the acquisition and reversal of learned associations, for instance by local infusions of substances that were shown to alter oscillations in other brain structures [e.g., GABA B and muscarinic receptor antagonists (Leung and Shen, 2007) as well as blockers of I h (Glasgow and Chapman, 2008)]. Second, further experiments may examine whether information on negative outcome predictions is also temporally structured by way of oscillatory activity, and how positive predictions about noningestible rewards are coded.…”
Section: Discussionmentioning
confidence: 99%